The Institutionalization of Shakespeare Studies in the United Kingdom - Sawyer, Robert (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
This essay is devoted to Shakespearean criticism in the UK between 1920 and 1940. I begin by examining the origins of Shakespeare study at Oxford and Cambridge, by figures such as I. A. Richards (1929) and William Empson (1930). I follow this by looking at F. R. Leavis and his journal Scrutiny, but I also trace his influence on his fellow Cambridge colleagues highlighting instances where they collaborated, as did Caroline Spurgeon with Arthur Quiller-Couch (the latter two co-editors of the New Cambridge Shakespeare series, 1921-1966) on the famous 1921 study for the British Board of Education entitled “The Teaching of English in England”—also referred to as The Newbolt Report, after the chairman of the committee, Sir Henry Newbolt.